1974
DOI: 10.1017/s0022112074002059
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the flow of thin liquid sheets in hot atmospheres

Abstract: A study has been made of the flow and disintegration of thin liquid sheets in combustion gases up to temperatures of 950°C. It is found that below 300°C sheet breakdown occurs through the growth of antisymmetric Kelvin–Helmholtz waves. Above this temperature high frequency symmetric waves and localized disturbances are superimposed on the sheet and disintegration then occurs by the combined action of aerodynamic waves and perforations, the contribution of the latter predominating with increasing temperature. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The estimated values of the electric field are of the same order of magnitude as the fields that are used in ordinary electrostatic sprayers, which utilize charging electrodes. This provides further evidence that the break-up process observed in the experiments of Clark and Dambrowski (1974) is indeed electro-hydrodynamical in nature.…”
Section: Concluslonsupporting
confidence: 64%
“…The estimated values of the electric field are of the same order of magnitude as the fields that are used in ordinary electrostatic sprayers, which utilize charging electrodes. This provides further evidence that the break-up process observed in the experiments of Clark and Dambrowski (1974) is indeed electro-hydrodynamical in nature.…”
Section: Concluslonsupporting
confidence: 64%
“…The reason is that wave disintegration is caused by aerodynamic forces which are proportional to the density of the surrounding gas. This reasoning has indeed been confirmed both by experiments in which liquids were sprayed into a vacuum chamber (Fraser et al 1962) and by experiments in which liquids were sprayed into hot flames (Clark and Dombrowski 1974). Perforated-sheet disintegration has recently also been observed in black liquor sprays injected into a full-size kraft recovery boiler (Adams et al 1990b).…”
Section: Primary Break-upmentioning
confidence: 71%
“…Such changes might be caused by, for example, the heat transfer from the hot gas to the liquid and the corresponding changes in the density, viscosity and surface tension of the liquid, or by the growth and explosions of vapor bubbles inside the liquid. Experiments have shown that the heat transfer from a flame to the liquid sheet significantly changes the atomization process and increases the average size of the drops (Clark and Dombrowski 1974, Walklate et al 1991. On the other hand, experiments and numerical calculations on the break-up of liquid jets have shown that the evaporation of the liquid may decrease the average size of the drops (Schetz e< al.…”
Section: Primary Break-upmentioning
confidence: 99%